The relationship between athletes’ self-esteem and perceived social support: the mediating effect of decentering and the moderating effect of training years - Huang, Xianbang; Li, Ling (Frontiers in Psychology, 2025)
ObjectiveThis study aimed to investigate the relationship between athletes’ Self-esteem(SE) and The Perceived Available Support in Sports Questionnaire(PASS-Q), with a particular focus on the mediating role of Decentering and the moderating effect of training years.MethodsA total of 354 athletes (198 males and 156 females) from various sports were surveyed using the Rosenberg Self-Esteem Scale, The Decentering Scale for Sport, and The Perceived Available Support in Sports Questionnaire. Correlation analysis, regression analysis, and PROCESS macro modeling were employed to examine the hypothesized relationships.Results(1) Athletes’ SE is significantly positively correlated with Decentering and PASS; (2) Decentering played a mediating role in the relationship between SE and PASS; (3) Training years moderated the direct effect of SE on PASS, such that the effect was stronger among athletes with longer training years.ConclusionSE not only directly promotes athletes’ PASS but also indirectly enhances it through Decentering. Furthermore, training years serve as a boundary condition for this relationship. These findings provide theoretical insights and practical implications for improving athletes’ psychological resilience and social adaptation.